2020
DOI: 10.13057/biodiv/d210409
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical diversity and antimicrobial properties of methanol extract of several cultivars of Catharanthus roseus using GC-MS

Abstract: Abstract. Samiyarsih S, Fitrianto N, Proklamasiningsih E, Juwarno, Muljowati JS. 2020. Phytochemical diversity and antimicrobial properties of methanol extract of several cultivars of Catharanthus roseus using GC-MS. Biodiversitas 21: 1332-1344. Catharanthus roseus (L.) G is an important medicinal plant to evaluate the possibility of novel pharmaceuticals since most of the bacterial pathogens are developing resistance against antibiotics. This research aimed to determine the phytochemical diversity of methanol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…The density of stomata-trichomes and cuticle thickness of sweet potatoes leaves correlated with the intensity of leaf scab disease caused by pathogens Sphaceloma batatas (Pradana et al 2017). Samiyarsih et al (2020) reported that different cultivars of one species almost gave different structures, phytochemical compounds, and different biological activities.…”
Section: Anatomical Profile Of Paradermal Sectionmentioning
confidence: 99%
“…The density of stomata-trichomes and cuticle thickness of sweet potatoes leaves correlated with the intensity of leaf scab disease caused by pathogens Sphaceloma batatas (Pradana et al 2017). Samiyarsih et al (2020) reported that different cultivars of one species almost gave different structures, phytochemical compounds, and different biological activities.…”
Section: Anatomical Profile Of Paradermal Sectionmentioning
confidence: 99%